2003
DOI: 10.1046/j.1439-0531.2003.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Techniques for Sperm Selection in Fresh and Frozen‐Thawed Stallion Semen

Abstract: The objective of this research was to improve the techniques in processing chilled and frozen-thawed horse semen. In a preliminary experiment (Exp. I), different techniques for sperm selection and preparation [Swim-up, Glass wool (GW) filtration, Glass wool Sephadex (GWS) filtration; Percoll] were tested for their suitability for equine spermatozoa and results were compared with the routine procedure by dilution (Exp. I). In the main experiment (Exp. II), two sperm preparation techniques (GWS, Leucosorb) refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
3
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 21 publications
(24 reference statements)
7
50
3
5
Order By: Relevance
“…The GWS filtration of stallion spermatozoa improved both sperm quality (129) and mare pregnancy rates after deep-horn insemination with low sperm numbers (130). Leukosorb filters also removed defective spermatozoa from stallion semen with an efficiency comparable to GWS (131). Compared to other microspin chromatography column separation methods, the use of glass wool yielded the highest sperm motility in stallions (132).…”
Section: Glass Wool and Other Filtration Methodsmentioning
confidence: 99%
“…The GWS filtration of stallion spermatozoa improved both sperm quality (129) and mare pregnancy rates after deep-horn insemination with low sperm numbers (130). Leukosorb filters also removed defective spermatozoa from stallion semen with an efficiency comparable to GWS (131). Compared to other microspin chromatography column separation methods, the use of glass wool yielded the highest sperm motility in stallions (132).…”
Section: Glass Wool and Other Filtration Methodsmentioning
confidence: 99%
“…Processing low-quality stallion semen with one layer of Percoll resulted in an improvement in sperm quality, although there was no improvement for "normal" ejaculates [18]. In contrast, sperm quality in "normal" stallion ejaculates was improved by single-layer centrifugation (SLC) using Androcoll-E, a new commercially available species-specific colloid for equine spermatozoa [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Sharma et al [3] showed that although it was possible to improve sperm quality in human ejaculates of low initial quality, no improvement in sperm quality was seen when "normal" human ejaculates were processed in this manner. Sieme et al [4] obtained similar results using one layer of Percoll ™ for stallion semen.…”
Section: Introductionmentioning
confidence: 68%